Ethmoiditis during Autoimmune Hepatitis Treatment: A Case Report - C, Elia; V, Boano; E, Battaglia; M, Grassini (Archives of Clinical and Medical Case Reports, 2020)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease, characterized by the elevation of aminotransferases, presence of anti-nuclear antibody or anti-smooth muscle antibody, elevated immunoglobulin G (IgG), and interface hepatitis/plasma-lymphocytic inflammation based on histology. The disease can be serious, and if left untreated, it can lead to cirrhosis of the liver and eventual liver failure. The recommended treatment for AIH includes corticosteroids and azathioprine. Azathioprine (AZA) is indicated in immunosuppressive regimens as an adjunct to immunosuppressive agents that form the mainstay of treatment. AZA is indicated either alone or in combination with corticosteroids and/or other drugs and procedures in several diseases. There are potential dangers in the use of AZA; they should therefore not be prescribed unless the patient can be adequately monitored for toxic effects throughout the duration of therapy. We present here the case of a 50-year-old female, with autoimmune hepatitis on AZA therapy who developed ethmoiditis.